The Effect of Organizational Culture on Production Department Employee Performance at PT. Shinkobe Engineering - Fahrullah (Formosa Journal of Science and Technology, 2022)
This study aims to examine the effect of organizational culture on the performance of employees of PT Shinkobe Engineering. Data collection was carried out by distributing questionnaires. The results are shown by looking at the tcount of the organizational culture variable of 7.809 which is greater than the ttable of 1.999 with a significance level of 0.000, the significance level is lower than 0.05. Research also shows that there is a positive and significant influence given by organizational culture which has a strong influence in influencing PT Shinkobe Engineering's employee performance optimally, the resulting R value (correlation) is 0.618 so it can be said that organizational culture and performance are positively related. While the coefficient of determination R2 (R Square) is 0.381, which means that the ability of organizational culture variables to influence employee performance at PT Shinkobe Engineering is 38.1%, while 61.9% is contributed by other factors not observed in this study.